Age at menarche and body mass index among school going adolescent girls in Bharatpur metropolitan city Chitwan - Bhusal, Pujan; Khatiwada, Sushma; Poudyel, Pragati (Journal of Chitwan Medical College, 2021)
Background: Menarche is a milestone for adolescent girls. The age of menarche is influenced by genetic, social status, place, race, ethnicity, nutritional and physical activity. There have been many studies on age at menarche but very few in this part of the country. This study aimed to assess the age of menarche and Body mass index among school going adolescent girls in Bharatpur Metropolitan city Chitwan. Methods: Total participants of 163 adolescent girls in this cross-section study were chosen from three private schools of Bharatpur Metropolitan city during June-September 2021. A pre-tested self-administrated questionnaire for menarche and anthropometric measurements were carried out for body mass index. The data were then entered to Statistical Package for Social Science (IBM SPSS, version 20) for the analysis. Results: The study revealed that the age at menarche ranged from 10-14 years of age. BMI of students ranged from 14.68-40.26 with 47.2% of the study population being a healthy weight. Girls having the habit of exercise/yoga attained menarche at 12years or after 12 years whereas girls having no habit had their menarche before 12 years of age. Conclusions: Our finding from the present study forms a baseline to estimate the mean age of menarche. Physically, inactive adolescents were more likely to see menarche earlier than the average age. Many girls were seen overweight as well. Regular exercise and a healthy life style need to be promoted among school going adolescent.